The uses and gratifications of Twitter in Egypt after Jan 25 Revolution - Habib, Yousra (AUC Knowledge Fountain, 2012)
In 2011 social media became one of the most powerful tools for socio-political mobilization in the Arab world. â We Are All Khaled Saidâ page on Facebook helped Egyptians to organize their January 25 protests and Twitter helped them spreading news, photos, and videos of what was going on in Egypt. After Jan 25 Revolution people realized the importance and the power of Social Media and the number of Egyptian Twitter users dramatically increased. This study aimed to investigate the motives for using Twitter among Egyptian Twitter users and what the gratifications obtained from using it are. The study also tried to determine whether Egyptian Twitter users consider Twitter a credible source of news and if this is related to their trust in the state-owned media. A survey was conducted on a convenience and snowball sample of 560 Twitter users to examine the Uses and Gratifications of Twitter in Egypt. The results of the study revealed that Egyptian users mainly use Twitter to satisfy their surveillance needs, it also proved that Egyptian Twitter users do not trust their state-owned media and do not perceive it as a credible source of news, hence they rely on social media where Twitter is their primary source of news especially in time of crisis and for breaking news